2018
DOI: 10.1080/17482631.2018.1484219
|View full text |Cite
|
Sign up to set email alerts
|

Promoting well-being through group drumming with mental health service users and their carers

Abstract: Purpose: Music has been linked with well-being across clinical and community settings. Yet, research has focused on assessment of single dimensions of well-being and on the typical receiver of support services. Acknowledging the burden that a caring role encompasses and integrating recent proposals for a multifaceted definition of well-being, we explore the extent to which group drumming interventions translate into multidimensional well-being change for both mental health service users and carers. Method: Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 68 publications
2
58
0
Order By: Relevance
“…Studies of music and sport students have suggested high levels of wellbeing (e.g., Malebo et al, 2007;Ascenso et al, 2018a), yet worrying levels of vocation-related physical and mental health problems (e.g., Hildebrandt et al, 2012;Bauman, 2016;Spahn et al, 2017;Schinke et al, 2018). Bearing in mind this paradox, and against a background which suggests there are generally poor levels of mental health in HE students, this study compared wellbeing and trait patterns in music, sport and other students.…”
Section: Discussionmentioning
confidence: 93%
“…Studies of music and sport students have suggested high levels of wellbeing (e.g., Malebo et al, 2007;Ascenso et al, 2018a), yet worrying levels of vocation-related physical and mental health problems (e.g., Hildebrandt et al, 2012;Bauman, 2016;Spahn et al, 2017;Schinke et al, 2018). Bearing in mind this paradox, and against a background which suggests there are generally poor levels of mental health in HE students, this study compared wellbeing and trait patterns in music, sport and other students.…”
Section: Discussionmentioning
confidence: 93%
“…Whether there are different causal effects of arts participation and cultural attendance on mental functioning remains to be explored further. But this proposed difference in mechanisms between the two types of engagement is supported by several intervention studies that have identified improvements in aspects of functioning such as self-efficacy, agency and purpose as a result of arts participation [47].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study with members of a mixed amateur choir found improved immune function (as measured by secretory immunoglobulin A [S-IgA] and cortisol) and affect (as measured by the Positive and Negative Affect Schedule – PANAS) after one session of singing ( Kreutz et al, 2004 ). Community drumming also features in recent studies as particularly useful for wellbeing promotion with vulnerable groups such as older populations ( Perkins and Williamon, 2014 ) as well as with mental health service users, where recent work highlighted positive changes at both psychological and biological levels after short interventions of six or ten sessions of group drumming ( Fancourt et al, 2016 ; Perkins et al, 2016 ; Ascenso et al, 2018 ). In academic settings, music-engagement activities emerge as significant contributors to wellbeing through both the enhancement of positive emotions and as facilitators of optimal functioning through potentiating creativity, self-efficacy ( Boyce-Tillman, 2000 ) and social skills ( Schellenberg et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%